Effect of Pre-Harvest Foliar Application of Citric Acid and Malic Acid on Chlorophyll Content and Post-Harvest Vase Life of Lilium cv. Brunello - Darandeh, Nafiseh; Hadavi, Ebrahim (Frontiers in Plant Science, 2012)
Preharvest use of citric acid is a novel method in vase life extension of cut flowers, which is reported on tuberose earlier and confirmed here on lilium. In this research citric acid (0, 0.075, 0.15 percent v/v) and malic acid (0, 0.075, 0.15 percent v/v) were used together two times during growth period of lilium plants in a randomized factorial design with three replications. The results point out that 0.15% citric acid had increased vase life from 13.1 to 14 days (α=0.05). The interesting finding was the effect of citric acid on bulbil weight, which was decreased from 8.6 gr to 2.9 gr in 0.15% citric acid per cut flower. Malic acid while having no effect on pre-mentioned traits surprisingly increased the chlorophyll content significantly. The interaction effect between citric acid and malic acid on vase life and chlorophyll content proved significant and was evident in results both as antagonistic and synergistic in various traits. In mean comparison of factor-levels, the effect of citric acid on vase-life extension was more prominent increasing it from 11.8 to 14.3 days in treatment with 0.15% citric acid and without malic acid compared to control treatment.